Chittagong Medical College: A Center for Shaping Professionals Since 1957 The Sojourn for Mission & Vision (Journal of Chittagong Medical College Teachers' Association, 2026)
Abstract not availableJCMCTA 2025 ; 36 (2) : 1-1a